The Effectiveness of Pictionary Games to Improve English Vocabulary at SMK N 1 Kersana Kabupaten Brebes - Pratika, Fika; Andini, Sukma Nur; Yulianti, Fitri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
Several speaking problems at SMKN 1 Kersana, Brebes Regency attracted researchers to conduct this research as an effort to help students in language learning. Researchers tried to see the effectiveness of playing the Pictionary Game on English speaking skills. This Pictionary game is a simple game and is applicable to all levels of students. The main function of this game is to develop creative thinking, improve grammar, vocabulary and pronunciation, develop students' courage in expressing ideas and create responsibility and cooperation towards their students. Because of these advantages, many researchers have used this game on language learning such as the effect of Pictionary Game on vocabulary mastery and researchers decided to see whether Pictionary Game is effective for students' speaking skills. This research was conducted using an experimental design. In collecting data, the researcher took the pre-test and post-test from class XI Accounting A and examined them to see whether the Pictionary game was effective or not. The results of the research found that the results of the initial test or pretest with an average score of 8.30, this shows that class XI accounting A students do not fully have much knowledge regarding vocabulary in English. From the results of the t test using the Paired sample test method, it can be seen that (2-tailed) with a significance value of 0.000, H_0 is rejected, and from a significance level of 0.000 < 0.05 it can also be concluded that H_1 is accepted. Because H_0 is rejected and H_1 is accepted, it can be concluded that there is an increase in the vocabulary understanding of class This can be seen from the difference in the average value, namely 12.39 or 34.4%. This means that the learning method using the pictonary game technique has proven to be effective in increasing the vocabulary understanding of class XI students at SMK Negeri 1 Kersana.